1996
DOI: 10.1097/00005768-199601000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of cross-country ski racing

Abstract: This study investigated the evolution of skiing velocity, cycle length, and cycle rate in elite and subelite skiers during cross-country ski races. Senior male cross-country skiers engaged respectively in a 30-km skating race (N = 34) or a 50-km classical race (N = 27) were videotaped as they skied two different sections of 30 m, a 7 degrees uphill, and a flat section. In the skating race, most skiers used the offset technique on uphill and the 2-skate on flat, while the preferred techniques during the classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
62
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 23 publications
14
62
0
1
Order By: Relevance
“…In this study, diVerences between the WC and the NL skiers in CL and CR were found at all measured speeds. Better skiers are also previously reported to have a longer CL in the skating technique (Bilodeau et al 1996;Rundell and McCarthy 1996;Stoggl and Muller 2009). Interestingly, in this study, both CL and CR increased with speed, up to V peak .…”
Section: Movement Characteristicssupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, diVerences between the WC and the NL skiers in CL and CR were found at all measured speeds. Better skiers are also previously reported to have a longer CL in the skating technique (Bilodeau et al 1996;Rundell and McCarthy 1996;Stoggl and Muller 2009). Interestingly, in this study, both CL and CR increased with speed, up to V peak .…”
Section: Movement Characteristicssupporting
confidence: 61%
“…It has been proposed that faster skiers have longer CL in the skating technique for two reasons. First, a longer CL might express higher maximal strength or power (Rundell and McCarthy 1996), and second, it might express a more eVective leg and pole push oV (Bilodeau et al 1996;Stoggl and Muller 2009). Particularly, this last factor is logically also related to enhanced eYciency.…”
Section: Movement Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the muscle activity during the eccentric phase has not been directly measured in the study of Candau et al (1994). Moreover, it has been reported that the technique studied in this investigation (V1 skate) is no longer generally employed by skiers on¯at or small gradient terrain (Bilodeau et al 1996). Thus, it is worth to reexamining the occurrence of SSC in the lower limbs using the V2-alternate (V2A) technique of ski skating.…”
Section: Introductionmentioning
confidence: 99%
“…Bilodeau et al (1996) investigated the Diagonal Technique of Cross-country Ski on DiŠerent Slopes diŠerences in speed, cycle length and cycle rate between the uphill section and the ‰at section during a 50 km o‹cial classical race. However, most skiers used the double pole technique on the ‰at section during that race.…”
Section: Introductionmentioning
confidence: 99%